Variations in the 24 h temporal patterns and time budgets of grazing, rumination, and idling behaviors in grazing dairy cows in a New Zealand system. (28th January 2023) - Iqbal, Muhammad Wasim; Draganova, Ina; Henry Morel, Patrick Charles; Todd Morris, Stephen
Abstract: This study investigated the variations in the temporal distributions and the lengths of times utilized for grazing, ruminating, and idling behaviors by grazing dairy cows over 24 h. Spring-calved lactating dairy cows ( N = 54) from three breeds, Holstein-Friesian (HFR), Jersey (JE), and KiwiCross (KC) in different lactations (1st, 2nd, 3rd) and with different breeding worth index values (103 < BW > 151) were selected. The cows were managed through a rotational grazing scheme and milked once a day at 0500 hours. The cows grazed mainly pasture and consumed additional feeds (maize silage and turnips) in the summer and autumn seasons. AfiCollar was used to record grazing and rumination behaviors (min/h) in the individual cows throughout the lactation period ( 270 d). The time neither utilized for grazing nor rumination was counted as idling behavior (min/h). A repeat measure design with PROC MIXED was performed in SAS considering the effects of breed, lactation, individual cow, the hour of the day, season, day within the season, and supplementary feed within the season to evaluate the difference in grazing, rumination, and idling behaviors. Hour of the day, season, day within season, and supplementary feed had significant effects on grazing, rumination, and idling behaviors. Regardless of the season and supplementary feed, cows spent most of the daytime grazing and most of the nighttime ruminating. Grazing activity remained consistently high throughout the day with two peaks around dawn and dusk and a short peak around midnight. Rumination activity remained high from the late evening until early morning. Grazing and ruminating patterns were similar between different breeds and lactations, however, JE cows grazed slightly longer than HFR and KC, and first-lactation cows grazed slightly longer than those in higher lactations. The onset and cessation of grazing activity by the cows were adjusted according to varying day lengths by season. Cows finished grazing earlier when they consumed additional supplements or silage along with pasture. Cows from different breed groups and lactations spent most of their 24 h grazing followed by ruminating and idling. Season and supplementary feed potentially affected the variations in behavior time budgets. These findings should support improving measures for grazing management to address pasture allocation and additional feed demands, and animal welfare in varying environmental and/or managemental conditions. Abstract : These findings could support the advancements in the measures for pasture and additional feed management to address individual animals' requirements and could improve animal welfare in varying environmental and managemental conditions Lay Summary: This study explored how grazing dairy cows pattern their essential such as including grazing, rumination, and idling, and how they distribute their time for those behaviors over 24 h. We used a group of spring-calved grazing dairy cows affiliated with different breeds, milking ages, and genetic merits and recorded their grazing and rumination behaviors for the whole milking period. An automated device, AfiCollar was used to continuously record minutes within an hour (min/h) utilized for grazing, rumination, and idling. The cows were mainly offered grass with some additional supplementary feeds on various days in summer and autumn and milked once a day at 0500 hours. Regardless of the breed, milking age, season, and supplementary feeds, grazing cows spent most of the daytime (from dawn to dusk) grazing and most of the nighttime ruminating, with a short grazing period around midnight. Cows adopted their grazing patterns according to varying day lengths during different seasons and finished grazing earlier when received supplementary feeds. Grazing cows allocated most of their time over 24 h for grazing followed by ruminating and idling. These findings could have implications to improve the measures for pasture management efficiency and additional feed demand, and animal welfare in varying environmental and/or managemental conditions.